A Analisis Faktor yang berhubungan dengan gangguan siklus menstruasi pada siswi - Velayati Kesuma; Triana Indrayani; Bunga Tiara Carolin (Health and Technology Journal (HTechJ), 2024)
Menstrual irregularities are typical in adolescent groups; in the world, the prevalence of menstrual cycle disorders in women in early adolescence is about 45%, and menstrual disorders can be severe. It may be a harbinger of the absence of ovulation; the amount of bleeding that is large and occurs over a long period can cause anaemia in adolescents. Factors associated with menstrual cycle disorders include stress, nutritional status, haemoglobin levels, physical activity, and sleep duration. This study aims to determine the relationship between stress, nutritional status, haemoglobin level, physical activity, and sleep duration with menstrual cycle disorders in female SMK Plus Trimitsa Cibinong in 2023. This research is quantitative correlational research; the method used is non-experiment with cross-sectional. The sample in this study amounted to 72 respondents, teen schoolgirls Class X-XII—sampling techniques using techniques purposive sampling, using the test Chi-square. There is a relationship between stress (p-value=0.002<0.05), nutritional status (p-value=0.006<0.05), haemoglobin levels (p-value=0.000<0.05), physical activity (p-value=0.015<0.05), and sleep duration (p-value=0.018<0.05), with menstrual cycle disorders in female SMK Plus Trimitsa Cibinong. The school can provide education and preventive, promotional efforts to prevent menstrual disorders on the side, and students can record the date of menstruation every month using a calendar or menstrual calendar application to find out how the menstrual cycle is going.